KONSEP PENGEMBANGAN PEDIDIKAN LIFE SKILLS DALAM LINGKUP MADRASAH - Mutaqin, Ade Zaenul (Program Studi Pendidikan Agama Islam, 2025)
This research is motivated by issues in Islamic education, as represented by madrasah, which have consistently been a subject of public debate over time. These issues primarily revolve around the low quality of education and the relevance of madrasah education to labour market needs. The objectives of this research are to understand the concept of life skills education, to explore the concept of education in madrasahs, and to design or develop a model for life skills education in madrasahs. The research method employs a qualitative approach in the form of a literature study. This involves collecting, analyzing, and interpreting data from various sources, such as books, journal articles, official documents, and other materials relevant to the research topic. The approach aims to gain an in-depth understanding of the concepts, theories, or phenomena under study. The research findings are as follows: (1) Life skills education develops practical skills that equip students to address various challenges in life. (2) Development of Life Skills Education in Madrasahs: This involves fostering the holistic development of human dimensions, including moral, ethical, intellectual, skill-based, health, artistic, and cultural aspects. These efforts aim to enhance life skills development, realized through the achievement of student competencies. Life skills education is integrated into the curriculum through learning activities in each subject and other activities conducted in madrasah.